Indonesian Politicians From One Stage to Another - Arrianie, Lely (Green Publisher, 2022)
After the Reform Era's birth in 1998, following the New Order regime's downfall that had controlled Indonesian politics for 32 years, two shows dominate the Indonesian political stage: freedom and violence. Politicians manage their roles on the front-stage, middle-stage, and backstage with the different political communication styles from those in the New Order era. Today, political communications in the Parliament tend to be more fluid as well as interactional, circular, convergent, and even transactional instead of linear, where political communicators, politicians, activists, professionals, and people deliver their aspirations to the political stage and political journalists in more open political message exchanges. All politicians should be wise in presenting their roles in the political stage shows, and social media that functions as the middle stage for political shows, which they should manage well to align political shows with political stages.